Systems biomarkers in psoriasis: Integrative evaluation of computational and experimental data at transcript and protein levels - TURANLI, BESTE; BEREKETOĞLU, CEYHUN; ARĞA, KAZIM YALÇIN (ELSEVIER SCIENCE BV, 2018)
Psoriasis is a complex autoimmune disease with multiple genes and proteins being involved in its pathogenesis. Despite the efforts performed to understand mechanisms of psoriasis pathogenesis and to identify diagnostic and prognostic targets, disease-specific and effective biomarkers were still not available. This study is compiled regarding clinical validation of computationally proposed biomarkers at gene and protein expression levels through qRT-PCR and ELISA techniques using skin biopsies and blood plasma. We identified several gene and protein clusters as systems biomarkers and presented the importance of gender difference in psoriasis. A gene cluster comprising of P13, IRF9, IFIT1 and NMI were found as positively correlated and differentially co-expressed for women, whereas SUB1 gene was also included in this cluster for men. The differential expressions of IRF9 and NMI in women and SUB1 in men were validated at gene expression level via qRT-PCR. At protein level, PI3 was abundance in disease states of both genders, whereas PC4 protein and WIF1 protein were significantly higher in healthy states than disease states of male group and female group, respectively. Regarding abundancy of PI3 and WIF1 proteins in women, and PI3 and PC4 in men may be assumed as systems biomarkers at protein level.
Keywords: Autoimmune disease; Gene clusters; Psoriasis; Systems biomarkers; SUSCEPTIBILITY LOCUS; INSULIN-RESISTANCE; GENDER-DIFFERENCES; EXPRESSION; NETWORK; CANCER; OMICS; IDENTIFICATION; HORMONES; TARGETS